Sealing tape with weak adhesive or no adhesive on one side
By setting different adhesive forces on the two main sides of the sealing tape, combining the polymer foam layer and the external pressure-sensitive adhesive layer or thermoplastic film, the problems of poor sealing effect and inconvenient application and disassembly in the prior art are solved, and high sealing and convenient use of sealing elements are achieved.
Patent Information
- Application Number
- CN202180008392.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-15
- Filing Date
- 2021-01-15
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-01-15
AI Technical Summary
In the prior art, it is difficult to achieve a high sealing effect when sealing the joints between the components, and the application and disassembly of the sealing elements are not easy enough.
Adhesive tapes with different peel adhesions (adhesion) on both main sides, including polymer foam layers and external pressure sensitive adhesive layers or external thermoplastic films, are used to achieve a high sealing effect and allow easy joint removal by this structure.
A sealing element with high sealing effect on air and moisture is realized and the possibility of simply opening the sealed gap again is provided, suitable for automated processing and with controlled compression characteristics.
Smart Images

Figure BDA0003732422120000228 
Figure BDA0003732422120000231
Abstract
Description
[0001] The present invention relates to the field of adhesive tapes, such as those commonly used in the home and in industry for connecting two substrates, as well as for other purposes, such as for protecting surfaces or for sealing. More particularly, it proposes a foam adhesive tape suitable for sealing, which has different adhesive powers on its two main sides or is provided with adhesive only on one of its two main sides.
[0002] In various industrial sectors, for example in construction and in vehicle construction, many structures require sealing. Sealing elements used for this purpose are often intended to seal gaps (such as those that almost inevitably arise when connecting two components) from the penetration of moisture and air in order to protect the components located behind them from damage caused thereby, such as corrosion. Mechanical joints (joints), such as those realized by screws, are generally unable to achieve adequate sealing.
[0003] Therefore, often, for example, silicone sealants are used to achieve a proper seal of the resulting joint. Such sealants are very reliable in their handling, but do require a certain amount of time to cure and therefore often cause difficulties associated with the process. This situation is similar to that of other structural adhesives / sealants, such as those based on epoxies or polyurethanes.
[0004] Silicone foams are also used as sealants, characterized by good flame retardant properties and their reusability. However, they are difficult to handle in automated operations and are also relatively expensive.
[0005] Butyl sealants are well established and inexpensive, but on the other hand they are difficult to control in terms of their metering and lack aging resistance. Moreover, at relatively high pressures they are often squeezed out of the gaps.
[0006] Elastic sealants such as rubber or styrene-butadiene rubber provide established sealing properties and are also highly temperature-stable. However, since they are not self-adhesive, they are difficult to use (process); moreover, they are inflexible (hard), so the corresponding sealing element must be exactly adapted to the gap to be sealed.
[0007] Polyurethane foams exhibit good compression properties and can be processed in automated operations; moreover, so-called foam-in-place applications are possible. Fluctuations in the dimensions of the foams in question are disadvantageous, and these materials are also susceptible to corrosion and destruction under the influence of certain cleaning products.
[0008] EPDM foams show a similar property profile; also with these, due to their irregular surface structure, only a limited sealing effect can be achieved.
[0009] In contrast, WO 2009 / 086056 A2 describes a so-called flashing tape, which is intended to provide moisture protection in construction applications. The tape discloses a construction comprising a viscoelastic core layer and at least one elastomeric outer layer; in addition, a pressure-sensitive adhesive layer may be included to adhere the tape to a substrate.
[0010] There is a continuing need for systems suitable for sealing a joint between two components. It is therefore an object of the present invention to provide an easily applied sealing element with a high sealing effect against air and moisture, which also offers the possibility of simply reopening the sealed gap.
[0011] A first general subject of the invention for achieving this object is an adhesive tape having different peel adhesion (adhesion) on two main sides, comprising:
[0012] a) a polymer foam layer, and
[0013] b) an outer pressure-sensitive adhesive layer and / or an outer thermoplastic film, each on one side of the polymer foam layer;
[0014] And it is characterized by
[0015] If the adhesive tape comprises an outer pressure-sensitive adhesive layer, the adhesive tape has a higher adhesion on its side provided with the outer pressure-sensitive adhesive layer than on the opposite side,
[0016] and / or
[0017] If the adhesive tape comprises an outer thermoplastic film, the adhesive tape has a lower adhesion on its side provided with the outer thermoplastic film than on the opposite side.
[0018] As already apparent, this adhesive tape can be advantageously used for sealing the joints between components, wherein on the one hand, allows simple, reliable and accurate application, and on the other hand allows easy disassembly of the joint. In addition, it is well adapted to automated processing and exhibits controlled compression properties.
[0019] In the sense of the present invention, the general term "tape" covers all sheet-like structures which are provided with a self-adhesive on one or both sides, such as films or film portions (segments) extending in two dimensions, tapes with an extended length and a limited width, tape portions (segments), labels, die-cut parts, etc., and corresponding multilayer arrangements.
[0020] Adhesive tapes or their adhesives are often lined with or protected by a so-called release liner, which is removed before applying the adhesive tape. The release liner is not part of the adhesive tape but is merely an aid for its production and / or storage.
[0021] The tape is typically provided as follows
[0022] - in fixed lengths, e.g. as a measured good, or
[0023] - Continuous product in the form of a roll (Archimedes screw) or a coil wound on a core.
[0024] Polymer foam layer
[0025] The adhesive tape of the invention comprises a polymer foam layer. "Polymer foam layer" or "polymer foam" refers to a material having open and / or closed cells distributed throughout its entire mass and having an apparent density lower than that of a polymeric skeleton substance. The expression "foam" means in particular that the layer in question comprises a structure consisting of gas-filled, often spherical or polyhedral pores (the pores being bounded by a liquid, semi-liquid, high-viscosity or solid pore support or by its own shell material) and that the structure is present in the respective layer in such a proportion that the density of the foamed layer is reduced relative to the density of the matrix material (i.e. the bulk of the non-gaseous material present in the pores separated from any own shell material).
[0026] The skeleton material (hereinafter also referred to as polymer foam matrix, foam matrix, matrix or matrix material) is according to the invention one or more polymers, which may have been blended with adjuvants. "Open cells" are voids within the foam, but are not completely surrounded by the skeleton material or its own shell material. "Closed cells" are voids that are completely surrounded by the skeleton material or its own shell material. The polymer foam layer of the adhesive tape of the invention is preferably a closed-cell foam.
[0027] It is generally preferred that the polymer foam layer, more particularly the matrix material of the polymer foam layer, comprises one or more polymers to an extent of at least 35% by weight, more preferably at least 50% by weight and very preferably at least 70% by weight, more particularly at least 80% by weight, for example at least 90% by weight, in each case based on the total weight of the polymer foam layer or the total weight of the matrix material. This polymer content can vary depending on the nature of the base polymer. Possible polymer foam layer polymers include: polyolefins, such as polyethylenes such as high density polyethylene (HDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE) and linear ultra low density polyethylene, polypropylene and polybutene; vinyl copolymers, such as polyvinyl chloride and polyvinyl acetate; olefin random or block copolymers, such as ethylene-methyl acrylate copolymers, ethylene-vinyl acetate copolymers and ethylene-propylene copolymers and ethylene-propylene-diene terpolymers (EPDM), and polyalkylenes prepared from a monomer mixture comprising: 1) a first olefin selected from ethylene, propylene or a mixture thereof, and 2) a second olefin selected from 1,2-olefins having 4 to 8 carbon atoms, such as 1,2-butene, 1,2-hexene or 1,2-octene; acrylonitrile-butadiene-styrene copolymers; acrylic polymers and copolymers; polycarbonates; polyimides; polyurethanes, such as thermoplastic polyurethanes, more particularly polyester-based thermoplastic polyurethanes; polyesters, such as polyethylene terephthalate; and combinations and blends of the foregoing polymers. Exemplary blends include polypropylene-polyethylene blends, PVC-nitrile rubber blends, polyurethane-polyolefin blends, polyurethane-polycarbonate blends, and polyurethane-polyester blends. Blends of thermoplastic polymers, elastomeric polymers, and combinations thereof may also be included. Other possible blends include styrene-butadiene copolymers, polychloroprenes such as chloroprene rubber, nitrile rubber, butyl rubber, polysulfide rubber, cis-1,4-polyisoprene, ethylene-propylene terpolymers such as EPDM rubber, silicone rubber, silicone-polyurea block copolymers, polyurethane rubber, natural rubber, acrylate rubber, thermoplastic rubbers such as styrene-butadiene block copolymers, styrene-isoprene-styrene block copolymers, styrene-ethylene / butylene-styrene block copolymers, styrene-ethylene / propylene-styrene block copolymers, thermoplastic polyolefin rubbers, and combinations thereof.
[0028] The one or more polymers of the polymer foam layer, more particularly the matrix material of the polymer foam layer, are preferably selected from: polyolefins; polyurethanes; polyvinyl chloride (PVC); blends of PVC and nitrile rubber; terpolymers of ethylene, propylene and non-conjugated dienes (EPDM); copolymers of ethylene and ethylene substituted with polar groups; blends of polyethylene and polymers formed from ethylene substituted with polar groups; poly(meth)acrylates; blends of poly(meth)acrylates and synthetic rubbers, and mixtures of two or more of the aforementioned polymers. Therefore, the polymer foam layer, more particularly the matrix material of the polymer foam layer, preferably comprises at least 35% by weight, more preferably at least 50% by weight and very preferably at least 70% by weight, more particularly at least 80% by weight, for example at least 90% by weight, based on the total weight of the polymer foam layer or the total weight of the matrix material, in each case, of one or more polymers selected from the group consisting of: polyolefins; polyurethanes; polyvinyl chloride (PVC); blends of PVC and rubber; terpolymers of ethylene, propylene and a non-conjugated diene (EPDM); copolymers of ethylene and ethylene substituted by polar groups; blends of polyethylene and polymers formed from ethylene substituted by polar groups; poly(meth)acrylates; blends of poly(meth)acrylates and synthetic rubbers, and mixtures of two or more of the aforementioned polymers. Particularly preferably, the matrix material of the polymer foam layer does not contain polymers other than one or more polymers selected from the following: polyolefins; polyurethanes; polyvinyl chloride (PVC); blends of PVC and rubber; terpolymers of ethylene, propylene and non-conjugated dienes (EPDM); copolymers of ethylene and ethylene substituted with polar groups; blends of polyethylene and polymers formed from ethylene substituted with polar groups; poly(meth)acrylates; blends of poly(meth)acrylates and synthetic rubbers, and mixtures of two or more of the foregoing polymers.
[0029] "Polyolefin" refers to a polymer of the general structure -[CH2-CR1R2-]n-, wherein R1 and R2 independently represent a hydrogen atom or a linear or branched saturated aliphatic or alicyclic group. The polyolefin is preferably polyethylene, polypropylene, polybutene or a mixture of these. The polyethylene here may include one or more of the following: conventional polyethylene types such as HDPE, LDPE, LLDPE, VLDPE, VLLDPE, MDPE (medium density PE), metallocene PE types such as mLLDPE and mHDPE, blends of these polyethylene types, and mixtures thereof. Polypropylene is preferably crystalline polypropylene, more preferably homopolypropylene (hPP). In a specific embodiment I of the polymer foam layer, the matrix material of the polymer foam layer does not contain a polymer other than one or more polyolefins.
[0030] The copolymer of ethylene and ethylene substituted by polar groups refers to a polymer of the general structure -[CH2-CR3R4-]n-, wherein R3 or R4 represents a hydrogen atom and the remaining substituents represent a group containing at least one oxygen atom in each case. The copolymer of ethylene and ethylene substituted by polar groups is preferably an ethylene-vinyl acetate copolymer (EVA), an ethylene-methyl acrylate copolymer (EMA), an ethylene-acrylate copolymer (EEA), an ethylene-acrylic acid copolymer (EAA), an ethylene-butyl acrylate copolymer (EBA), or a mixture of these. EVA preferably has a vinyl acetate content of 1-70% by weight, more preferably 3-30% by weight, more particularly 5-20% by weight. In a more specific variant of embodiment I of the polymer foam layer, the matrix material of the polymer foam layer does not contain polymers other than one or more copolymers formed by ethylene and ethylene substituted by polar groups. More particularly, in this case, the copolymer of ethylene and ethylene substituted by polar groups is an ethylene-vinyl acetate copolymer (EVA). Therefore, it is particularly preferred that, in this embodiment, the matrix material of the polymer foam layer comprises at least one ethylene-vinyl acetate copolymer (EVA). More particularly, the overall fraction (proportion) of all ethylene-vinyl acetate copolymers in the matrix material of the polymer foam layer is at least 50% by weight, more preferably at least 70% by weight and very preferably at least 80% by weight, more particularly at least 85% by weight, for example at least 90% by weight, in each case based on the total weight of the matrix material. Very particularly preferably, the matrix material contains no polymers other than one or more ethylene-vinyl acetate copolymers (EVA).
[0031] The matrix material of the polymer foam layer is preferably crosslinked. The crosslinking is preferably carried out before the foaming of the matrix material. The matrix material, which comprises a polymer selected from the group consisting of polyolefins and copolymers of ethylene and ethylene substituted by polar groups, is preferably crosslinked with electron beams. Also suitable are chemical crosslinking methods, for example crosslinking via grafted silane groups with hydrolyzable groups, which can then react with one another under the influence of moisture and catalysis; in addition, crosslinking via added silanes, which contain free-radically polymerizable double bonds and can react with free radicals formed in the polymer chains; and crosslinking via added peroxides, which likewise react with free radicals.
[0032] In embodiment II of the polymer foam layer, the polymer foam layer, more particularly the matrix material of the polymer foam layer, comprises at least one poly(meth)acrylate. "Poly(meth)acrylate" is a polymer obtainable by free radical polymerization of acrylic and / or methacrylic monomers and optionally further copolymerizable monomers. More particularly, "poly(meth)acrylate" is a polymer whose monomer base consists to an extent of at least 50% by weight of acrylic acid, methacrylic acid, acrylic acid esters and / or methacrylic acid esters, wherein acrylic acid esters and / or methacrylic acid esters are included at least in proportion, preferably to an extent of at least 30% by weight, based on the total monomer base of the polymer in question.
[0033] The polymer foam layer preferably comprises in total 40-99.9% by weight, more preferably in total 60-98% by weight, more particularly in total 75-95% by weight, for example in total 80-90% by weight of poly(meth)acrylates, in each case based on the total weight of the polymer foam layer. Either one (single) poly(meth)acrylate or two or more poly(meth)acrylates may be present; therefore, also in the remainder of the description, the plural expression "poly(meth)acrylates" and the expression "in total (total)" include in their meaning both the presence of one single poly(meth)acrylate and the presence of two or more poly(meth)acrylates.
[0034] The glass transition temperature of poly (meth) acrylate is preferably <0 ° C, more preferably between -20 and -50 ° C. According to the present invention, the glass transition temperature of the polymer block or polymer in the block copolymer is determined by means of dynamic scanning calorimetry (DSC). For this purpose, about 5 mg of untreated polymer sample is weighed into an aluminum crucible (volume 25 μl) and closed with a perforated lid. The measurement is performed using a DSC 204 F1 from Netzsch. The operation is carried out under nitrogen to inertize. The sample is initially cooled to -150 ° C, then heated to +150 ° C at a heating rate of 10K / min, and cooled to -150 ° C again. The subsequent second heating curve is run again at 10K / min and the change in heat capacity is recorded. The glass transition is identified as a step in the thermogram.
[0035] The poly(meth)acrylate preferably comprises at least one functional monomer copolymerized in proportion, particularly preferably a monomer that reacts with epoxy groups to form covalent bonds. Very preferably, the functional monomer copolymerized in proportion, particularly preferably a monomer that reacts with epoxy groups to form covalent bonds comprises at least one functional group selected from the group consisting of carboxylic acid groups, sulfonic acid groups, phosphoric acid groups, hydroxyl groups, anhydride groups, epoxy groups and amino groups; more particularly, it comprises at least one carboxylic acid group. Very preferably, the poly(meth)acrylate comprises acrylic acid and / or methacrylic acid copolymerized in proportion. All stated groups exhibit reactivity with epoxy groups, thus making the poly(meth)acrylate advantageously suitable for thermal crosslinking with introduced epoxides.
[0036] The poly(meth)acrylates may preferably be derived from the following monomer compositions:
[0037] a) at least one acrylate and / or methacrylate of the following formula (1):
[0038] CH2=C(R I )(COOR II ) (1),
[0039] Where R I is H or CH3 and R II is an alkyl group having 4 to 18 carbon atoms,
[0040] b) at least one ethylenically unsaturated monomer having at least one functional group selected from the group consisting of a carboxylic acid group, a sulfonic acid group, a phosphoric acid group, a hydroxyl group, an anhydride group, an epoxy group and an amino group;
[0041] c) Optionally further acrylates and / or methacrylates and / or ethylenically unsaturated monomers copolymerizable with component (a).
[0042] It is particularly advantageous to select monomers of component a) with a fraction of 45-99% by weight, monomers of component b) with a fraction of 1-15% by weight and monomers of component c) with a fraction of 0-40% by weight, the figures being based on the monomer mixture for the base polymer without the addition of possible additives such as resins etc.
[0043] Particularly preferably, the poly(meth)acrylate may be derived from the following monomer composition:
[0044] 65-99% by weight of 2-ethylhexyl acrylate and / or n-butyl acrylate,
[0045] 0-30% by weight of methyl acrylate,
[0046] 1-15 wt.% acrylic acid.
[0047] The one or more poly(meth)acrylates are preferably prepared by conventional free radical polymerization or controlled free radical polymerization. The poly(meth)acrylates can be prepared by copolymerizing the monomers using conventional polymerization initiators and optionally chain transfer agents, wherein the polymerization is carried out at conventional temperatures in bulk, in emulsion, for example in water or liquid hydrocarbons, or in solution.
[0048] The poly(meth)acrylates are preferably prepared by copolymerizing the monomers in a solvent, more preferably in a solvent having a boiling range of 50-150° C., more particularly 60-120° C., using 0.01-5 wt %, more particularly 0.1-2 wt % (in each case based on the total weight of the monomers) of polymerization initiator.
[0049] In principle, all customary initiators are suitable. Examples of free radical sources are peroxides, hydroperoxides and azo compounds, such as dibenzoyl peroxide, cumene hydroperoxide, cyclohexanone peroxide, di-tert-butyl peroxide, cyclohexylsulfonylacetyl peroxide, diisopropyl percarbonate, tert-butyl peroctoate and benzopinacol. A preferred free radical initiator is 2,2'-azobis(2-methylbutyronitrile) (from DuPont 67 TM ) or 2,2'-azobis(2-methylpropionitrile) (2,2'-azobisisobutyronitrile; AIBN; from DuPont 64 TM ).
[0050] Preferred solvents for the preparation of poly(meth)acrylates are alcohols such as methanol, ethanol, n-propanol and isopropanol, n-butanol and isobutanol, more particularly isopropanol and / or isobutanol; hydrocarbons such as toluene and more particularly mineral spirits with a boiling range of 60 to 120° C.; ketones, more particularly acetone, methyl ethyl ketone, methyl isobutyl ketone; esters such as ethyl acetate; and mixtures of the aforementioned solvents. Particularly preferred solvents are mixtures comprising isopropanol in an amount of 2 to 15% by weight, more particularly 3 to 10% by weight, based in each case on the solvent mixture used.
[0051] Preferably, the concentration is carried out after the preparation (polymerization) of the poly(meth)acrylate and the further processing of the poly(meth)acrylate is essentially solvent-free. The concentration of the polymer can be carried out in the absence of crosslinking agents and promoter substances. However, it is also possible to add one of these classes of compounds to the polymer just before the concentration, so that the concentration is then carried out in the presence of this or these substances.
[0052] After the concentration step, the polymer can be transferred to a compounder. An optional possibility is that concentration and compounding also take place in the same reactor. Further processing after concentration (compounding) preferably takes place in one or more extruders. In this case, the material is applied from the melt to a possible temporary support material and shaped into a layer by means of a calender roll.
[0053] The weight average molecular weight Mw of the poly(meth)acrylates is preferably in the range of 20 000-2 000 000 g / mol, very preferably in the range of 100 000-1 500 000 g / mol, most preferably in the range of 150 000-1 000 000 g / mol. For this purpose, it may be advantageous to carry out the polymerization in the presence of suitable polymerization chain transfer agents, such as mercaptans, halogen compounds and / or alcohols, to establish the desired average molecular weight.
[0054] The statements of the number average molecular weight Mn and the weight average molecular weight Mw are based on conventional determination by gel permeation chromatography (GPC) in this specification. The determination is carried out on 100 μl samples (sample concentration 4 g / l) that have undergone clarifying filtration. The eluent used is tetrahydrofuran with 0.1% by volume of trifluoroacetic acid. The measurement is carried out at 25°C.
[0055] The pre-column used was the following column: PSS-SDV type, 5 μm, 8.0mm*50mm (the data here and below are in the following order: type, particle size, porosity, inner diameter*length; =10 -10 m). The following column combination was used for separation: PSS-SDV type, 5 μm, as well as and Each 8.0 mm*300 mm (column from Polymer Standards Service; detection by means of a Shodex RI71 differential refractometer). The flow rate is 1.0 ml / min. Calibration in the case of poly(meth)acrylates is performed against PMMA standards (polymethyl methacrylate calibration) and in the other cases (resins, elastomers) against PS standards (polystyrene calibration).
[0056] Poly (meth) acrylate preferably has a polydispersity PD <4 and therefore has a relatively narrow molecular weight distribution. The material based thereon has particularly good shear strength after crosslinking, despite having a relatively low molecular weight. Moreover, the lower polydispersity enables easier processing by melt, because for roughly the same application properties, the flow viscosity is lower than that of a more widely distributed poly (meth) acrylate. Poly (meth) acrylates with narrow distribution can advantageously be prepared by anionic polymerization or by a controlled radical polymerization method, the latter being particularly suitable. The corresponding poly (meth) acrylate can also be prepared via N-oxyl groups. In addition, in an advantageous manner, atom transfer radical polymerization (ATRP) can be used for the synthesis of narrowly distributed poly (meth) acrylates, in which the initiator used preferably includes monofunctional or difunctional secondary or tertiary halides and, for the extraction of halides, includes a complex of Cu, Ni, Fe, Pd, Pt, Ru, Os, Rh, Co, Ir, Ag or Au. RAFT polymerization is also suitable.
[0057] The poly(meth)acrylates are preferably crosslinked by a linking reaction of the functional groups present therein with a thermal crosslinker, more particularly in the sense of an addition or substitution reaction. All thermal crosslinkers can be used:
[0058] - it ensures both a sufficiently long processing life so that no gelling occurs during the processing operation, more particularly the extrusion operation,
[0059] - and in turn leads to rapid postcrosslinking of the polymer to the desired degree of crosslinking at temperatures below the processing temperature, more particularly at room temperature.
[0060] The thermal crosslinkers are preferably used in an amount of from 0.1 to 5% by weight, more particularly from 0.2 to 1% by weight, based on the total amount of polymer to be crosslinked.
[0061] Also possible is crosslinking via complexing agents (also called chelates). An example of a preferred complexing agent is aluminum acetylacetonate.
[0062] The poly(meth)acrylates are preferably crosslinked by means of epoxides or by means of one or more substances containing epoxy groups. The substances containing epoxy groups are more particularly polyfunctional epoxides, i.e. those having at least two epoxy groups; thus, generally there is an indirect linking of those building blocks of the poly(meth)acrylates carrying functional groups. The substances containing epoxy groups may include both aromatic and aliphatic compounds.
[0063] Preferred epoxide crosslinking agents are, for example, cycloaliphatic epoxides such as 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (UVACure 1500).
[0064] The poly(meth)acrylates are more preferably crosslinked with the aid of a crosslinker-accelerator system ("crosslinking system") in order to obtain better control over the processing life, the crosslinking kinetics and the degree of crosslinking. The crosslinker-accelerator system preferably comprises as crosslinker at least one substance comprising epoxy groups and as accelerator at least one substance which has an accelerating effect on the crosslinking reaction with the aid of compounds comprising epoxy groups at temperatures below the melting temperature of the polymer to be crosslinked.
[0065] The accelerators used are particularly preferably amines.
[0066] In another embodiment III of the polymer foam layer, the polymer foam layer, more particularly the matrix material of the polymer foam layer, comprises at least one vinyl aromatic block copolymer. Preferably, the polymer foam layer, more particularly the matrix material of the polymer foam layer, comprises at least one vinyl aromatic block copolymer as follows:
[0067] - it comprises at least one polymer block A formed predominantly by polymerization of a vinyl aromatic compound, and
[0068] - it comprises at least one polymer block B formed predominantly by polymerization of conjugated dienes, wherein the fraction of 1,2-linked conjugated dienes in the B block is less than 30% by weight, preferably less than 20% by weight (which can be obtained by means of 1 H NMR).
[0069] In the embodiment III considered herein, the vinyl aromatic block copolymer described above is preferably present in the polymer foam as the elastomeric component. When the polymer foam comprises multiple elastomeric components, it is preferably present in the polymer foam at least 50 weight percent, based on the total weight of all elastomeric components.
[0070] The polymer blocks A of the preferred vinyl aromatic block copolymers are formed predominantly by polymerization of vinyl aromatic compounds. This means that block A typically originates from polymerization in which more than 50% by weight of the monomers used are vinyl aromatic compounds. More preferably, polymer block A originates from polymerization in which only vinyl aromatic compounds are used as monomers.
[0071] The polymer block B of the preferred vinyl aromatic block copolymer is formed predominantly by polymerization of conjugated dienes. This means that block B originates from polymerization in which more than 50% by weight of the monomers used are conjugated dienes. More preferably, polymer block B originates from polymerization in which only conjugated dienes are used as monomers.
[0072] The fraction of 1,2-linked conjugated dienes in the B block of the preferred vinyl aromatic block copolymer is less than 30% by weight, preferably less than 20% by weight. More preferably, this fraction is less than 15% by weight, more particularly 8-12% by weight. The fraction of 1,2-linked conjugated dienes in the B block means the weight fraction of conjugated dienes that have been copolymerized by 1,2-addition (as opposed to 1,4-addition), based on the total monomer composition used in the preparation of polymer block B. The 1,2-addition of conjugated dienes leads to vinyl-type side groups in polymer block B, while the 1,4-addition of conjugated dienes leads to vinyl functional groups in the main chain of polymer block B. The 1,2-addition of conjugated dienes thus means that the monomers are introduced into the polymer chain via positions C1 and C2 or via positions C3 and C4 (for example, in the case of isoprene as conjugated diene). In contrast, in the 1,4-addition of conjugated dienes, the monomers are introduced via positions C1 and C4.
[0073] The vinyl aromatic block copolymers preferably have AB, ABA, (AB) n , (AB) n X or (ABA) n X structure, where
[0074] - the blocks A are independently of one another polymers formed by polymerization of at least one vinyl aromatic compound,
[0075] - the blocks B are independently of one another polymers formed by polymerization of conjugated dienes having 4 to 18 carbon atoms,
[0076] -X is a group of a coupling agent or an initiator, and
[0077] -n is an integer ≥ 2.
[0078] Particularly preferably, in embodiment III, all vinyl aromatic block copolymers of the polymer foam layer of the present invention are AB, ABA, (AB) as described above. n , (AB) n X or (ABA) n Block copolymers of structure X. Thus, the polymer foam layer may also include a mixture of different vinyl aromatic block copolymers having the structures described above.
[0079] Block B is also referred to as rubbery (rubbery) block or soft block, and block A is also referred to as glassy (glassy) block or hard block. Particularly preferably, at least one vinyl aromatic block copolymer of the polymer foam layer has an AB, ABA, (AB)2X, (AB)3X or (AB)4X structure, wherein A, B and X have the above definitions. Very particularly preferably, all vinyl aromatic block copolymers have an AB, ABA, (AB)2X, (AB)3X or (AB)4X structure, wherein A, B and X have the above definitions. More particularly, in embodiment III, the polymer foam layer comprises a mixture of block copolymers having an AB, ABA, (AB)2X, (AB)3X or (AB)4X structure, the mixture more preferably comprising at least a diblock copolymer AB and / or a triblock copolymer ABA and / or (AB)2X, more particularly a mixture of a diblock copolymer (AB) and a triblock copolymer (ABA), which consists, for example, of two vinyl aromatic block copolymers having different weight ratios of the diblock copolymer (AB) and the triblock copolymer (ABA).
[0080] The vinyl aromatic block copolymers preferably have a diblock copolymer fraction of 0-70% by weight, more preferably 15-65% by weight, more particularly 30-60% by weight, very preferably 40-60% by weight, for example 51.5-55% by weight.
[0081] The block copolymers obtained from the A and B blocks may comprise identical or different B blocks.
[0082] In the preferred vinylaromatic block copolymers, more particularly in the preferred styrene block copolymers, the fraction of polyvinylaromatic compound, more particularly polystyrene, is preferably at least 12% by weight, more preferably at least 18% by weight, very preferably at least 25% by weight and likewise preferably at most 45% by weight and more preferably at most 35% by weight.
[0083] Instead of the preferred polystyrene blocks, polymer blocks based on homopolymers and copolymers containing other aromatic compounds having a glass transition temperature of more than 75° C. can also be used as vinyl aromatic compounds. Preferred homopolymer and / or copolymer blocks are those based on C8-C12 aromatic compounds, for example α-methylstyrene. Identical or different A blocks may be present.
[0084] The polymer block A is preferably formed predominantly by polymerization of styrene and / or α-methylstyrene. Block A may therefore take the form of a homopolymer or a copolymer.
[0085] Particularly preferably, block A is polystyrene. Very particularly preferably, the vinylaromatic block copolymer has polystyrene end blocks.
[0086] The polymer block B is preferably formed predominantly by polymerization of conjugated dienes selected from the group consisting of butadiene, isoprene, ethylbutadiene, phenylbutadiene, pentadiene, hexadiene, ethylhexadiene, dimethylbutadiene, α-farnesene and β-farnesene, and any desired mixtures of these monomers; like block A, it may be present as a homopolymer or as a copolymer. Particularly preferably, block B is formed predominantly by polymerization of butadiene and / or isoprene. Very particularly preferably, block B is polybutadiene; polybutadiene has even better aging behavior than polyisoprene.
[0087] The A blocks are also referred to in the context of the present invention as "hard blocks". The B blocks are correspondingly also referred to as "soft blocks" or "elastomeric blocks". This reflects the selection of the blocks according to their glass transition temperature, which is preferably at least 25°C, more particularly at least 50°C for the A blocks, and preferably at most 25°C, more particularly at most -25°C, and more particularly at most -50°C for the B blocks.
[0088] In embodiment III, the fraction of the vinyl aromatic block copolymer, more particularly the styrene block copolymer as a whole in the polymer foam layer is preferably at least 35% by weight, based on the total weight of the polymer foam layer. Such a fraction advantageously improves the cohesion of the polymer foam layer.
[0089] The maximum fraction of vinyl aromatic block copolymers, more particularly styrene block copolymers as a whole in the polymer foam layer is preferably not more than 75% by weight, more particularly not more than 65% by weight, very preferably not more than 55% by weight.
[0090] The polymer foam of embodiment III preferably comprises at least one tackifier resin. In principle, one or more tackifier resins may be present. Thus, the foam is advantageously endowed with pressure-sensitive adhesive properties.
[0091] According to the general understanding of the skilled person, a "tackifier resin" is understood to be a low molecular weight oligomeric or polymeric resin which increases the adhesion (tack, inherent tack) of a pressure-sensitive adhesive compared to an otherwise identical pressure-sensitive adhesive but without the tackifier resin.
[0092] The tackifier resin preferably has a DACP (diacetone alcohol cloud point) of >0°C, more preferably >10°C, more particularly >30°C, and a softening temperature (ring and ball) of ≥70°C, preferably ≥100°C.
[0093] Particularly preferably, the corresponding tackifier resin has a DACP of not more than 45° C., if no isoprene blocks are present in the elastomeric phase, or a DACP of not more than 60° C., if isoprene blocks are present in the elastomeric phase. Particularly preferably, the corresponding tackifier resin has a softening temperature of not more than 150° C.
[0094] The tackifier resin is preferably a hydrocarbon resin; more particularly, it is chosen from hydrogenated and non-hydrogenated polymers of dicyclopentadiene; unhydrogenated, partially, selectively or fully hydrogenated hydrocarbon resins based on C5, C5 / C9 or C9 monomer streams (streams), and polyterpene resins based on α-pinene and / or β-pinene and / or δ-limonene. These tackifier resins can be used alone or in a mixture. In principle, resins that are solid at room temperature and resins that are liquid at room temperature can be used. Hydrogenated or unhydrogenated tackifier resins that also contain oxygen can optionally be present in a maximum fraction of up to 25% by weight, based on the total mass of tackifier resins contained in the polymer foam, examples of these being rosin and / or rosin ester resins and / or terpene-phenol resins in the polymer foam of embodiment III.
[0095] Particularly preferably, the tackifier resin is an unhydrogenated hydrocarbon resin, more particularly based on α-pinene. These resins provide polymer foams which have not only high cohesion but also advantageously very high adhesion, in particular also at high temperatures.
[0096] The polymer foam in the case of embodiment III preferably comprises 20 to 60 wt %, more preferably 30 to 50 wt %, of at least one tackifier resin, in each case based on the total weight of the polymer foam.
[0097] Foaming
[0098] In principle, foams can be produced in two ways: on the one hand, by the action of a propellant (blowing agent) gas, whether added as such or produced by a chemical reaction; on the other hand, by introducing hollow spheres into a material matrix. Foams produced in the latter way are called composite foams.
[0099] Physical propellants are any naturally occurring atmospheric materials that are in gaseous form at the temperature and pressure at which the foam emerges from the nozzle. Physical propellants can be introduced, i.e. injected, into the matrix material in the form of a gas, a supercritical fluid or a liquid. The selection of the physical propellant used depends on the desired properties of the resulting foam. Other factors considered when selecting a propellant are its toxicity, vapor pressure characteristics, ease of handling, and solubility associated with the polymer material used. Combustible propellants such as pentane, butane, and other organic materials such as hydrofluorocarbons and hydrochlorofluorocarbons can be used; but non-combustible, non-toxic, non-ozone-degrading propellants are preferred because they are easier to use, encounter fewer problems with their impact on the environment, etc. Preferred physical propellants are carbon dioxide, nitrogen, SF6, nitrogen oxides, perfluorinated liquids such as C2F6, noble gases such as helium, argon and xenon, air (typically a mixture of nitrogen and oxygen), and mixtures of these materials.
[0100] Another alternative possibility is to use chemical propellants for foaming. Suitable chemical propellants include a mixture of sodium bicarbonate and citric acid, dinitrosopentamethylenetetramine, p-toluenesulfonylhydrazide, 4,4'-oxybis(benzenesulfonylhydrazide), azodicarbonamide (1,1'-azobiscarbonamide), p-toluenesulfonyl semicarbazide, 5-phenyltetrazolyl, 5-phenyltetrazolyl analogs, diisopropyl hydrazinedicarboxylate, 5-phenyl-3,6-dihydro-1,3,4-oxadiazacyclohexane-2-one and sodium borohydride.
[0101] The polymer foam layer preferably comprises microspheres; in this case, it is at least foamed using the microspheres. When it is foamed only with the aid of microspheres, it is a composite foam.
[0102] "Microspheres" are understood to mean hollow microspheres having a thermoplastic polymer shell, which is elastic and thus expandable in its ground state. These spheres are filled with low-boiling liquids or liquefied gases. The shell materials used include in particular polyacrylonitrile, PVDC, PVC or polyacrylates. Conventional low-boiling liquids include in particular lower alkane hydrocarbons, such as isobutane or isopentane, which are encapsulated in the polymer shell under pressure in the form of a liquefied gas.
[0103] The action on the microspheres (particularly by exposure to heat) causes the polymer shell to soften. At the same time, the liquid propellant gas inside the shell changes to its gaseous state. In this case, the microspheres stretch irreversibly and undergo a three-dimensional expansion. The expansion ends when the internal and external pressures are balanced. Since the polymer shell is retained, the result is a closed-cell foam.
[0104] Various types of microspheres are commercially available and differ essentially in their size (6 to 45 μm in diameter in the unexpanded state) and in the onset temperature required for their expansion (75 to 220° C.). Unexpanded microsphere types are also available in the form of aqueous dispersions with a solid fraction or microsphere fraction of about 40-45% by weight, and additionally also in the form of polymer-bound microspheres (masterbatches) (e.g., in ethylene-vinyl acetate at a microsphere concentration of about 65% by weight). Like the unexpanded microspheres, both the microsphere dispersions and the masterbatches are thus suitable for producing polymer foam layers.
[0105] The polymer foam layer can also be produced using so-called pre-expanded microspheres. In the case of this group, the expansion takes place before introduction into the polymer matrix.
[0106] It is also possible to produce polymer foams using expanded particles; that is, using expanded or expandable beads, in particular of polystyrene, polypropylene, thermoplastic polyurethane or cellulose acetate. Thus, particles consisting of a plastic which has itself undergone foaming are introduced into the polymer matrix and a reduction in density occurs. The particles can also be placed in the polymer matrix in an unfoamed manner and only then be foamed. Furthermore, the polymer foam can also consist of optionally pre-expanded beads which are thermally connected to one another, more particularly welded, so that in this case no further surrounding matrix is present.
[0107] The polymer foam may include aging inhibitors, for example primary antioxidants such as hindered phenols, secondary antioxidants such as phosphites or thioethers and / or C-radical scavengers. In addition, there may be, for example, light stabilizers such as UV absorbers or hindered amines; antiozonants; metal deactivators and / or processing aids.
[0108] The polymeric foam may additionally include fillers such as silica, glass (ground or in bead form), alumina, zinc oxide, calcium carbonate, titanium dioxide, carbon black, and the like, as well as pigments, dyes, and / or optical brighteners.
[0109] External pressure-sensitive adhesive layer
[0110] Pressure-sensitive adhesives (PSAs) or pressure-sensitive adhesive compositions are understood in the present invention and according to common usage to be materials that are permanently tacky and adhesive at least at room temperature. A PSA is characterized in that it can be applied to a substrate by pressure and remains adhered there, without further limiting the time of application of the pressure or exposure to the pressure. Usually, although it depends in principle on the precise nature of the PSA and on the substrate, temperature and atmospheric humidity, the influence of a minimum pressure of short duration (not exceeding a brief period of gentle contact) is sufficient to achieve the adhesive effect, while in other cases longer periods of exposure to higher pressures may also be necessary.
[0111] PSAs have specific characteristic viscoelastic properties which lead to permanent viscosity and tack. These adhesives are characterized by the fact that when they are mechanically deformed, there is a process of viscous flow and also the formation of elastic restoring forces. The two processes have a certain relationship to each other in terms of their respective proportions, which depends not only on the precise composition, structure and degree of crosslinking of the PSA, but also on the rate and duration of deformation, and on the temperature.
[0112] Proportional (in a certain proportion) viscous flow is necessary for the realization of adhesion. Only the viscous component (component) produced by the macromolecule with relatively high mobility allows to effectively wet the substrate to be bonded and effectively flow to the substrate to be bonded. High viscous flow component leads to high viscosity (also referred to as surface adhesion), and therefore often also leads to high adhesion. Highly crosslinked systems, crystalline polymers or polymers with glassy solidification lack flowable components, and usually lack viscosity or at least only have very little viscosity.
[0113] A certain proportion of elastic restoring forces is necessary for the realization of cohesion. They are generated, for example, by very long-chain macromolecules with a high degree of curl and by physically or chemically crosslinked macromolecules, and they allow the forces acting on the adhesive bond to be transmitted. As a result of these restoring forces, the adhesive bond is able to adequately withstand long-term loads acting on it (for example in the form of continuous shear loads) for relatively long periods of time.
[0114] In order to more precisely describe and quantify the extent of the elastic and viscous components, as well as the relationship between the components, the variables of storage modulus (G') and loss modulus (G") are used and can be determined with the aid of dynamic mechanical analysis (DMA). G' is a measure of the elastic component of a substance, G" is a measure of the viscous component of a substance. Both variables depend on the deformation frequency and the temperature.
[0115] The variables can be determined using a rheometer. In this case, the material to be investigated is exposed to a sinusoidally oscillating shear stress, for example in a plate / plate arrangement. In the case of an instrument operating with shear stress control, the deformation is measured as a function of time and the time shift of this deformation is measured relative to the introduction of the shear stress. This time shift is called the phase angle δ.
[0116] The storage modulus G' is defined as follows: G' = (τ / γ)·cos(δ) (τ = shear stress, γ = deformation, δ = phase angle = phase shift between the shear stress vector and the deformation vector). The loss modulus G" is defined as follows: G" = (τ / γ)·sin(δ) (τ = shear stress, γ = deformation, δ = phase angle = phase shift between the shear stress vector and the deformation vector).
[0117] At 23°C,0 Up to 10 1 rad / s deformation frequency range, both G' and G" are at least partially within 10 3 Up to 10 7 Pa, then the composition is particularly regarded as a PSA and is particularly defined as such for the present invention. "Partially" means that at least a portion of the G' curve lies within the range of 10 0 rad / sec (including endpoints) up to 10 1 rad / s (including the end points) and the deformation frequency range (abscissa) from the range 10 3 Pa (including endpoints) to 10 7 The range of G' values (ordinate) of Pa (including the endpoints) is within the window spanned by , and at that time at least a portion of the G" curve is also within the corresponding window.
[0118] The outer pressure-sensitive adhesive layer comprises one or more poly(meth)acrylates, preferably to an extent of at least 50% by weight, more preferably at least 70% by weight, very preferably at least 90% by weight, more particularly at least 95% by weight, for example at least 97% by weight, in each case based on the total weight of the pressure-sensitive adhesive layer.
[0119] The outer pressure-sensitive adhesive layer comprises one or more poly(meth)acrylates, particularly preferably to an extent of at least 50% by weight, more preferably at least 70% by weight, very preferably at least 90% by weight, more particularly at least 95% by weight, for example at least 97% by weight, in each case based on the total weight of the pressure-sensitive adhesive layer, which are derived from the following monomer compositions:
[0120] Mon1) at least one acrylate and / or methacrylate of formula (2)
[0121] CH2=C(R III )(COOR IV ) (2),
[0122] Where R III is H or CH3 and R IV is an alkyl group having 4 to 12 carbon atoms;
[0123] Mon2) at least one ethylenically unsaturated monomer having at least one functional group selected from the group consisting of a carboxylic acid group, a sulfonic acid group, a phosphoric acid group, a hydroxyl group, an anhydride group, an epoxy group and an amino group;
[0124] Mon3) optionally at least one acrylate and / or methacrylate of formula (3).
[0125] CH2=C(R V)(COOR VI ) (3),
[0126] Where R V is H or CH3 and R VI It is an alkyl group having 1 to 3 carbon atoms.
[0127] In each case one or more monomers Mon1, Mon2 and Mon3 may be present independently of one another in the monomer composition.
[0128] The monomer Mon1 is preferably present in the monomer composition to an extent of at least 70% by weight, more preferably to an extent of at least 80% by weight, in each case based on the total weight of the monomer composition.
[0129] The monomer Mon2 is preferably present in the monomer composition in an amount of 1 to 15% by weight, based on the total weight of the monomer composition.
[0130] If present at all, monomer Mon3 is preferably present in the monomer composition at 5 to 15 wt %, based on the total weight of the monomer composition.
[0131] The monomer Mon1 preferably comprises at least one branching monomer. Particularly preferably, the monomer a) is selected from the group consisting of n-butyl acrylate, n-butyl methacrylate, n-pentyl acrylate, n-pentyl methacrylate, n-pentyl acrylate, n-hexyl acrylate, n-hexyl methacrylate, n-heptyl acrylate, n-octyl acrylate, n-octyl methacrylate, n-nonyl acrylate, isobutyl acrylate, isooctyl acrylate, isooctyl methacrylate, 2-ethylhexyl acrylate and 2-ethylhexyl methacrylate, 2-propylheptyl acrylate and isobornyl acrylate. Particularly preferably, the monomer Mon1 is selected from the group consisting of n-butyl acrylate, 2-ethylhexyl acrylate and isobornyl acrylate.
[0132] The monomer Mon2 is preferably selected from acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, aconitic acid, dimethacrylic acid, β-acryloxypropionic acid, trichloroacrylic acid, vinylacetic acid, vinylphosphonic acid, maleic anhydride, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, 6-hydroxyhexyl methacrylate, allyl alcohol, glycidyl acrylate and glycidyl methacrylate. Acrylic acid is particularly preferably present as monomer Mon2.
[0133] Preferably present as monomer Mon3, if present at all, is methyl acrylate.
[0134] Particularly preferably, the poly(meth)acrylate of the outer pressure-sensitive adhesive layer is derived from a monomer composition comprising:
[0135] 70 to 95% by weight of 2-ethylhexyl acrylate, n-butyl acrylate and / or isobornyl acrylate; more particularly n-butyl acrylate and 2-ethylhexyl acrylate;
[0136] 1-15 wt% acrylic acid; and
[0137] 0-15% by weight of methyl acrylate.
[0138] More particularly, the poly(meth)acrylate of the outer pressure-sensitive adhesive layer is derived from a monomer composition comprising:
[0139] 70 to 95% by weight of 2-ethylhexyl acrylate, n-butyl acrylate and / or isobornyl acrylate; more particularly n-butyl acrylate and 2-ethylhexyl acrylate;
[0140] 1-15 wt% acrylic acid; and
[0141] 0-15% by weight of methyl acrylate.
[0142] The poly(meth)acrylate of the outer pressure-sensitive adhesive layer is preferably crosslinked thermally, more particularly covalently and / or coordinately. Preferred covalent crosslinkers are epoxide compounds; preferred coordinate crosslinkers are aluminum chelates.
[0143] The weight average molecular weight Mw of the poly(meth)acrylate of the outer pressure-sensitive adhesive layer is preferably 20 000-2 000 000 g / mol, more preferably 100 000-1 500 000 g / mol, more particularly 200 000-1 200 000 g / mol. The figures for the average molecular weight Mw in this description are based on determinations by gel permeation chromatography (see experimental part).
[0144] External thermoplastic film
[0145] “External thermoplastic film” means that the thermoplastic film faces outwards and thus completes the structure of the adhesive tape with its side.
[0146] The thermoplastic film has no adhesive properties or has adhesive properties only to a very small extent, so that it closes the side with weaker adhesion in any conceivable configuration of the adhesive tape of the invention comprising an external thermoplastic film. Thus, if the adhesive tape does comprise an external thermoplastic film, it has lower adhesion on its side provided with the external thermoplastic film than on the opposite side, or it has no adhesion on its side provided with the external thermoplastic film.
[0147] The thermoplastic film preferably comprises at least one polymer selected from the group consisting of thermoplastic polyolefins (TPE-E or TPO), more particularly thermoplastic polyolefin elastomers (POE); and thermoplastic polyolefin plastomers (POP); thermoplastic polystyrene elastomers (TPE-S or TPS), more particularly styrene block copolymers (SBC); thermoplastic polyurethane elastomers (TPE-U or TPU); thermoplastic polyester elastomers and copolyesters (TPE-E or TPC); thermoplastic copolyamides (TPE-A or TPA); and thermoplastic vulcanizates and crosslinked thermoplastic polyolefin elastomers (TPE-V or TPV).
[0148] More particularly, the thermoplastic film consists of at least one polymer, particularly preferably one polymer, chosen from: thermoplastic polyolefins (TPE-E or TPO), more particularly thermoplastic polyolefin elastomers (POE); and thermoplastic polyolefin plastomers (POP); thermoplastic polystyrene elastomers (TPE-S or TPS), more particularly styrene block copolymers (SBC); thermoplastic polyurethane elastomers (TPE-U or TPU); thermoplastic polyester elastomers and copolyesters (TPE-E or TPC); thermoplastic copolyamides (TPE-A or TPA); and thermoplastic vulcanizates and crosslinked thermoplastic polyolefin elastomers (TPE-V or TPV).
[0149] Tape structure
[0150] The structure or layer sequence of the adhesive tape of the present invention includes a variety of variations. In one embodiment, the structure of the adhesive tape of the present invention is limited to a polymer foam layer and an outer pressure-sensitive adhesive (PSA) layer. Therefore, in this case, the adhesive tape of the present invention consists of:
[0151] a) a polymer foam layer, and
[0152] b) Outer PSA layer.
[0153] In this case, the necessarily weaker adhesion on the side opposite to the outer PSA layer results in the fact that the exposed side of the polymer foam layer has weaker adhesion than the PSA layer. In this embodiment, the polymer foam layer preferably corresponds to the polymer foam layer of embodiment II described here; the polymer foam layer, more particularly the matrix material of the polymer foam layer, therefore preferably comprises at least one poly(meth)acrylate. All more detailed configurations described in the case of embodiment II of the polymer foam layer are correspondingly valid here.
[0154] In principle, the invention also includes embodiments in which an outer PSA layer is arranged on both sides of the polymer foam layer in each case. Of course, according to the core concept of the invention, in this case the two outer PSA layers are not identical and differ in particular in their adhesiveness.
[0155] In another embodiment of the present invention, the adhesive tape of the present invention consists of:
[0156] a) a polymer foam layer, and
[0157] b) External thermoplastic film.
[0158] In this embodiment, the polymer foam layer preferably corresponds to the polymer foam layer of embodiment III described here; the polymer foam layer, more particularly the matrix material of the polymer foam layer, therefore preferably comprises at least one vinyl aromatic block copolymer. All more detailed configurations described in the case of embodiment III of the polymer foam layer are correspondingly valid here.
[0159] The polymer foam layer in this embodiment has in particular sufficient (pressure-sensitive) adhesiveness to enable a sufficiently strong bond to be achieved between itself and the outer thermoplastic film.
[0160] In a further embodiment of the invention, the adhesive tape consists of:
[0161] a) a polymer foam layer;
[0162] b1) an outer PSA layer on one side of the polymer foam layer; and
[0163] b2) An outer thermoplastic film on the side of the polymer foam layer opposite to the outer PSA layer.
[0164] In this embodiment, the polymer foam layer preferably corresponds to the polymer foam layer of embodiment II described here; the polymer foam layer, more particularly the matrix material of the polymer foam layer, therefore comprises at least one poly(meth)acrylate. All more detailed configurations described in the case of embodiment II of the polymer foam layer are correspondingly valid here.
[0165] The polymer foam layer in this embodiment has in particular sufficient (pressure-sensitive) adhesiveness to enable a sufficiently strong bond between itself and the outer thermoplastic film to be achieved.
[0166] In further embodiments, the tape comprises, in addition to the polymer foam layer:
[0167] b1) an outer PSA layer on one side of the polymer foam layer; and
[0168] b2) an outer thermoplastic film on the side of the polymeric foam layer opposite the outer PSA layer; and
[0169] c) an additional PSA layer on the side of the polymeric foam layer opposite to the outer PSA layer.
[0170] The additional PSA layer in this embodiment is therefore located between the polymer foam layer and the outer thermoplastic film; preferably, it connects the polymer foam layer to the outer thermoplastic film.
[0171] For the further PSA layer, the comments made with regard to the outer PSA layer apply. Preferably, the further PSA layer and the outer PSA layer are identical in their composition; more particularly, they are identical not only in their composition but also in their layer thickness.
[0172] In this embodiment as well, the polymer foam layer preferably corresponds to the polymer foam layer of embodiment II described here; the polymer foam layer, more particularly the matrix material of the polymer foam layer, therefore preferably comprises at least one poly(meth)acrylate. All the more detailed configurations described in the case of embodiment II of the polymer foam layer are correspondingly valid here.
[0173] use
[0174] A further subject of the invention is the use of the adhesive tape according to the invention for sealing a joint between two components. Advantageously, the adhesive tape according to the invention allows rapid bonding and thus rapid production of a seal without slipping and without the need for curing. A watertight seal that is not susceptible to corrosion can be provided. Moreover, disassembly of the joint is made easier, since the component joined with the weaker bonding side can be removed more easily.
[0175] The joint between the two components is preferably produced in a manner other than by adhesive bonding; particularly preferably, the joint between the components is a mechanically realized joint, for example by means of a screw connection.
[0176] The two components are in principle arbitrary; the term "component" is to be understood in a very broad sense. The two components are preferably the housing and the cover of a vehicle battery; particularly preferably, when this joint is sealed, the weaker adhesive side of the adhesive tape faces the cover. In addition, the component can also belong to an electronic device, for example to a smartphone or the like.
[0177] It is also preferred that, in the case of its use according to the invention, the adhesive tape according to the invention is removed from a cross-wound reel; in particular, this step is automated. Example
[0178] Test Method
[0179] Gel Permeation Chromatography for Molecular Weight Determination
[0180] The molecular weight data in this specification are based on determination by gel permeation chromatography. The determination was performed on 100 μl of sample (sample concentration 4 g / l) which had undergone clarification filtration. The eluent used was tetrahydrofuran with 0.1% by volume of trifluoroacetic acid. The measurement was performed at 25° C. The precolumn used was the following column: PSS-SDV type, 5 μ, ID 8.0mm·50mm. The following columns were used for separation: PSS-SDV type, 5μ, as well as and Each ID 8.0 mm x 300 mm (column from Polymer Standards Service; detected using Shodex RI71 differential refractometer). Flow rate 1.0 ml / min. Calibration against PMMA standards (polymethyl methacrylate calibration).
[0181] Water Permeability:
[0182] 5 mm wide strips were cut from the adhesive tape to be investigated and adhered to a square metal plate (external dimensions 80 mm×80 mm×5 mm). Here, the strips were arranged so that they formed a closed square outline. The ends of the strips each joined flush with the side of the next strip end.
[0183] Inside the square, a paste (KMnO4) is then applied, which undergoes a clear color change to violet when in contact with water. At this point, the same metal plates are placed on the structure and screwed. The screws are located outside the square of the tape strip. With the help of 2 spacers, each 1 mm thick, the distance between the metal plates is fixed to exactly 2 mm. The structure ensures that the water-reactive paste is in a closed space within the tape strip. The penetration of water will be recognized by the color change and indicates that the tape lacks water-impermeability.
[0184] The entire sample is now placed in a water bath, which is subsequently placed in an autoclave. A small superatmospheric pressure of 0.3 bar is initially applied; in a second test, a superatmospheric pressure of 3 bar then simulates a 30 m water column. After 30 minutes of storage under water in the autoclave, the superatmospheric pressure is reduced, the assembly is removed, and the sample is investigated for the color change of KMnO4. The color change indicates the water permeability of the tape; the absence of a color change indicates water impermeability (result "water-permeable yes / no").
[0185] Re-separability of bonded substrates (simulating re-separation of bonded battery covers; re-openability):
[0186] At a distance of 30 mm from the edge of the plate, the tape is applied once to an aluminum plate (450×250 mm, 2.5 mm thickness) with the more adhesive side. Another aluminum plate (450×250 mm, 1 mm thickness) with the same dimensions is applied to the free side (from above). A 2 mm thick gasket is inserted into the joint on each side, after which the assembly is pressed (compressed) in a screw clamp. Afterwards, the aluminum plate is screwed using the holes present in the corners of the plate for this purpose.
[0187] The assembly thus produced is stored in a conditioning chamber at 40° C. and 100% relative humidity for 10 days. After removal, it is conditioned for a further 24 hours at 23° C. and 50% relative humidity.
[0188] Then, the screws and washers were removed and on one of the shorter sides, a tightened band was inserted into the joint, which was connected to a testing machine (Zwick). The upper (1 mm thick) plate was pulled apart at an angle of 90° and a speed of 300 mm / min, and the maximum force required for this was measured. Table 1 reports the average value from three measurements.
[0189] Tape used:
[0190] A- 61102 (closed-cell EPDM rubber foam, coated with acrylate adhesive on one side, total thickness 3200 μm; tesa)
[0191] B- ACX plus 70730 High Resistance (double-sided acrylic foam tape, coated with acrylate PSA on both sides, total thickness 2900 μm; tesa), laminated on one side with a thermoplastic polyurethane film ( U04 / PE, 30μm; Bayer)
[0192] C- ACX plus 70730 High Resistance, acrylate PSA applied only on one side, acrylate foam is therefore exposed on one side (see B, total thickness 2850 μm; tesa)
[0193] D- 92111HiP – High initial Performance, bonded to itself 3 times, total thickness 3300 μm; tesa); laminated on one side with a thermoplastic polyurethane film ( U04 / PE, 30μm; Bayer)
[0194] E- ACX plus 70730 High Resistance (double-sided acrylic foam tape, coated with acrylic PSA on both sides, total thickness 2900 μm; tesa); Comparative Example
[0195] Table 1: Test results
[0196]
[0197]
[0198] Vgl.=Comparative Example
Claims
1. Use of an adhesive tape for sealing a joint between a housing and a cover of a vehicle battery or between two components in an electronic device, wherein the adhesive tape has different adhesive forces on two main sides, the adhesive tape consisting of: a) a polymer foam layer, and b) an outer thermoplastic film on one side of the polymer foam layer; Features The adhesive tape has a lower adhesive force on its side provided with the outer thermoplastic film than on the opposite side, wherein the outer thermoplastic film is composed of at least one polymer selected from the group consisting of thermoplastic polyolefins; thermoplastic polystyrene elastomers; thermoplastic polyurethane elastomers; thermoplastic polyester elastomers and copolyesters; thermoplastic copolyamides; and thermoplastic vulcanizates and crosslinked thermoplastic polyolefin elastomers.
2. The use according to claim 1, characterized in that The polymer foam layer comprises, to an extent of at least 35 wt %, based on the total weight of the polymer foam layer, one or more polymers selected from the group consisting of polyolefins; polyurethanes; polyvinyl chloride (PVC); blends of PVC and nitrile rubber; terpolymers of ethylene, propylene and non-conjugated dienes (EPDM); copolymers of ethylene and ethylene substituted with polar groups; blends of polyethylene and polymers formed from ethylene substituted with polar groups; poly(meth)acrylates; blends of poly(meth)acrylates and synthetic rubbers; and mixtures of two or more of the foregoing polymers.
3. The use according to claim 1 or 2, characterized in that The polymer foam layer includes at least one poly(meth)acrylate.
4. The use according to claim 1 or 2, characterized in that The polymer foam layer includes microspheres.
5. The use according to claim 2, characterized in that The polymer foam layer includes the one or more polymers to an extent of at least 50 wt %, based on the total weight of the polymer foam layer.
6. The use according to claim 5, characterized in that The polymer foam layer includes the one or more polymers to an extent of at least 70 wt %, based on the total weight of the polymer foam layer.
7. The use according to claim 5, characterized in that The polymer foam layer includes the one or more polymers to an extent of at least 80 wt %, based on the total weight of the polymer foam layer.
8. The use according to claim 5, characterized in that The polymer foam layer includes the one or more polymers to an extent of at least 90 wt %, based on the total weight of the polymer foam layer.
9. The use according to claim 2, characterized in that The matrix material of the polymer foam layer does not contain polymers other than one or more polymers selected from the following: polyolefins; polyurethanes; polyvinyl chloride (PVC); blends of PVC and nitrile rubber; terpolymers of ethylene, propylene and non-conjugated dienes (EPDM); copolymers of ethylene and ethylene substituted with polar groups; blends of polyethylene and polymers formed from ethylene substituted with polar groups; poly(meth)acrylates; blends of poly(meth)acrylates and synthetic rubbers, and mixtures of two or more of the foregoing polymers.
10. The use according to claim 3, characterized in that The poly(meth)acrylates are polymers whose monomer base consists to an extent of at least 50% by weight of acrylic acid, methacrylic acid, acrylic acid esters and / or methacrylic acid esters, wherein the acrylic acid esters and / or methacrylic acid esters are comprised to an extent of at least 30% by weight, based on the total monomer base of the polymer in question.
11. The use according to claim 3, characterized in that The polymer foam layer includes a total of 40 to 99.9 wt % of poly(meth)acrylate, based on the total weight of the polymer foam layer.
12. The use according to claim 3, characterized in that The glass transition temperature of the poly(meth)acrylate is <0°C.
13. The use according to claim 3, characterized in that The poly(meth)acrylate is derived from the following monomer composition: a) at least one acrylate and / or methacrylate of the following formula (1): CH2=C(R I )(COOR II ) (1), Where R I is H or CH3 and R II is an alkyl group having 4 to 18 carbon atoms, b) at least one ethylenically unsaturated monomer having at least one functional group selected from the group consisting of a carboxylic acid group, a sulfonic acid group, a phosphoric acid group, a hydroxyl group, an acid anhydride group, an epoxy group and an amino group; c) Optionally further ethylenically unsaturated monomers copolymerizable with component (a).
14. The use according to claim 13, characterized in that Further ethylenically unsaturated monomers c) are further acrylates and / or methacrylates.
15. The use according to claim 13, characterized in that The poly(meth)acrylate is derived from the following monomer composition: 65-99% by weight of 2-ethylhexyl acrylate and / or n-butyl acrylate, 0-30% by weight of methyl acrylate, 1-15 wt% acrylic acid.
16. The use according to claim 3, characterized in that The weight average molecular weight Mw of the poly(meth)acrylate is in the range of 20,000-2,000,000 g / mol.
17. The use according to claim 1, characterized in that The polymer foam layer includes at least one vinyl aromatic block copolymer.
18. The use according to claim 1, characterized in that The joint between the two components is a mechanically realized joint.
Citation Information
Patent Citations
Multilayer flashing tape
WO2009086056A2
Hand-tearable double-sided pressure-sensitive adhesive tape
US20170226384A1
Multi-layer adhesive tape with resin-modified adhesive
WO2019229150A1
Fish-mouth-resistant waterproofing membrane
WO2019236112A1